CteG is a Chlamydia trachomatis effector protein that associates with the Golgi complex of infected host cells - Pais, Sara V. (2019)
Chlamydia trachomatis is a bacterial pathogen causing ocular and genital infections in humans. C. trachomatis multiplies exclusively inside host cells within a characteristic vacuole, from where it manipulates host cells by injecting them with type III secretion effector proteins. Here, we identified CteG as the first C. trachomatis effector associated with the Golgi. For this, C. trachomatis strains expressing candidate effectors fused to a double hemagglutinin (2HA) tag were constructed. Then, among these strains, immunofluorescence microscopy revealed that CteG-2HA was delivered into the cytoplasm of infected cells. Between 16-20 h post-infection, CteG-2HA mostly associated with the Golgi; however, CteG-2HA also appeared at the host cell plasma membrane, and at 30 or 40 h post-infection this was its predominant localization. This change in the main localization of CteG-2HA was independent of intact microfilaments or microtubules. Ectopic expression of different regions of CteG (656 amino acid residues) in uninfected cells revealed that its first 100 residues contain a Golgi targeting region. Although a C. trachomatis cteG mutant did not display a defect in intracellular multiplication, CteG induced a vacuolar protein sorting defect when expressed in Saccharomyces cerevisiae. This suggested that CteG might function by subverting host cell vesicular transport.